Pembelajaran Berkarakteristik Inovatif Abad 21 Pada Materi Kemandirian Karir Peserta Didik Dengan Metode Pembelajaran Berbasis Masalah (Pbl) Di Smk Negeri 1 Adiwerna Tegal - Deker Raharjo (Universitas Pancasakti Tegal, 2018)
Innovative learning is a learning strategy that emphasizes the delivery of learning materials to students in the form of expository, inquiry, problem-based learning, improving thinking skills, cooperative learning, contextual learning, affective learning and scientific approaches. The formation of student character that needs to be developed in the pillars of national education which refers to the processing of values ​​in the areas of mind, feeling, physical or body, and processing the heart which becomes the spirit in moving thoughts, feelings, and will or known as thinking, feeling, exercising. heart and sport. Problem-based learning or Problem Based Learning (PBL) is a learning model that can help students to be active and independent in developing problem-solving thinking skills through searching data so that solutions are obtained rationally and authentically